Dermatological manifestations of COVID-19: a practical summary of the current state of knowledge - Martyna Sławińska; Roman Nowicki (Przegląd Dermatologiczny, 2020)
While COVID-19 initially appeared to be manifested primarily by respiratory symptoms, it is now known to be a multi-organ disease, also with dermatological manifestations. Cutaneous symptoms in patients with COVID-19 have a wide clinical spectrum. They may appear at any stage of the disease or as its sole manifestation. Further research is necessary to clarify the pathogenesis of these changes, their prognostic significance and therapeutic management. This article summarizes the current knowledge about changes occurring in the skin, mucous membranes and nails of patients diagnosed with COVID-19 and addresses the issue of drug-induced skin changes associated most common treatments of COVID-19.